Non-monotonic decrease of coal permeability with depth in highly compressional tectonic settings: A case study in the Bide-Santang Basin, SW China. (June 2020) - Kang, Yongshang; Jiang, Shanyu; Deng, Ze; Ma, Yuan Zee; Wang, Jin; Gu, Jiaoyang; Sun, Hansen
Abstract: Coal permeability dependence on depth has been studied and discussed for a long time. However, the scattered distribution of coal permeability versus depth, and specifically the non-monotonic permeability decrease, in highly compressional tectonic settings has not been fully understood. This paper takes the Bide-Santang Basin, SW China, as a case study to discuss the non-monotonic decrease of coal permeability with depth. The results show that three regime intervals, including the uppermost normal regime interval, the middle mixed-regime interval and the deep normal regime interval, are identified in the Bide-Santang Basin. A tri-segmented linear model provides a better fit of coal permeability than a single linear model does. Coal permeability in the uppermost normal regime interval is characterized by exceptionally high values and quick decrease rate with increasing depth, in comparison with that in other intervals. The middle mixed-regime interval is characterized by a permeability increasing trend with depth, related primarily to the increase of horizontal differential stress in this interval. In the deep normal regime interval, the horizontal differential stress does not show any obvious trend, and coal permeability resumes its decreasing trend with depth. This study reveals the primary role of the horizontal differential stress, besides the effective stress, in controlling coal permeability in highly compressional tectonic settings characterized by stress regime transitions. Highlights: Three stress regime intervals are identified in the Bide-Santang Basin. A tri-segmented linear model provides a better fit of non-monotonic decrease of permeability. Increasing permeability is related primarily to the increase of differential stress. The increase of differential stress is related to regime transition from reverse to strike-slip.